Population Pharmacokinetics of Viloxazine Extended‐Release Capsules in Pediatric Subjects With Attention Deficit/Hyperactivity Disorder. (8th August 2021) - Nasser, Azmi; Gomeni, Roberto; Wang, Zhao; Kosheleff, Alisa R.; Xie, Lanyi; Adeojo, Lilian W.; Schwabe, Stefan
Abstract: Viloxazine extended‐release capsules (viloxazine ER; Qelbree) is a novel nonstimulant, recently approved by the US Food and Drug Administration for the treatment of ADHD in pediatrics. Here, we characterize the pharmacokinetics (PK) of viloxazine and its major metabolite, 5‐HVLX‐gluc, using a population PK model and evaluate the impact of 1‐4 days of missed viloxazine ER doses on viloxazine PK. Data from 4 phase 3 trials in pediatric subjects treated with viloxazine ER were used to establish the PK model. Covariate analysis was conducted on the final base model. The impact of 1‐4 days of missed doses on steady‐state viloxazine PK was evaluated using Monte Carlo simulations. A 1‐compartmental linear model with first‐order absorption and elimination of the parent drug and first‐order metabolite formation and elimination properly described the population PK of viloxazine and 5‐HVLX‐gluc. Body weight impacted the systemic exposure of viloxazine and 5‐HVLX‐gluc. Predicted PK parameters at steady state (mean ± standard deviation) in children receiving viloxazine ER were determined. Cmax was 1.60 ± 0.70 μg/mL at 100 mg, 2.83 ± 1.31 μg/mL at 200 mg, and 5.61 ± 2.48 μg/mL at 400 mg. AUC0‐t was 19.29 ± 8.88 μg·h/mL at 100 mg, 34.72 ± 16.53 μg·h/mL at 200 mg, and 68.00 ± 28.51 μg·h/mL at 400 mg. PK parameters for adolescents receiving viloxazine ER were also determined. Cmax was 2.06 ± 0.90 μg/mL at 200 mg, 4.08 ± 1.67 μg/mL at 400 mg, and 6.49 ± 2.87 μg/mL at 600 mg. AUC0‐t was 25.78 ± 11.55 μg·h/mL at 200 mg, 50.80 ± 19.76 μg·h/mL at 400 mg, and 79.97 ± 36.91 μg·h/mL at 600 mg. Simulations revealed that, regardless of the duration of the dosing interruption, viloxazine concentration returned to steady‐state levels after approximately 2 days of once‐daily dosing of viloxazine ER.